Stress in parents of children with autism: A Malaysian experience - Ahmad Basri, Nadzirah; Nik Hashim, Nik Nur Wahidah (International Islamic University Malaysia, 2019)
This study examines differences in parental stress between parents of Autism Spectrum Disorder (ASD) children (n=21) and Typically Developed (TD) children (n=41) in Malaysia. This study also compares the ages of parents of ASD children with parents of TD children with stress as a variable in these parents. Parents completed the Parental Stress Index (brief Malay version) and a socio-demographic questionnaire. Parents with ASD children were found to be significantly more stressed compared to parents of TD children (p<0.001). Significant scores were also found in the Parent-Child Dysfunctional Interaction (P-CDI) sub-scale (p<0.001) as well as Difficult Child (DC) and Parental Distress (PD) sub-scales with lower significance (p<0.05). Results also indicate that the 30-35-year-old age group among ASD parents was significantly found to be more stressed compared with parents of TD children of the same ages. Implications of the findings regarding support and intervention for families with ASD are also discussed.